2022
DOI: 10.1111/nph.18020
|View full text |Cite
|
Sign up to set email alerts
|

MYB43 as a novel substrate for CRL4PRL1 E3 ligases negatively regulates cadmium tolerance through transcriptional inhibition of HMAs in Arabidopsis

Abstract: Summary Controlled stability of proteins is a highly efficient mechanism to direct diverse processes in plants. A key regulatory system for protein stability is given by the CULLIN‐RING E3 ligases (CRLs). In this work, MYB43 is identified as a novel target of a CUL4‐DDB1‐PRL1 (PLEIOTROPIC REGULATORY LOCUS 1)‐RING E3 ligase (CRL4PRL1 E3 ligase). Its stability depends on the presence of PRL1, a WD40‐containing protein functioning as a substrate receptor of the CRL4 E3 ligases. Genetic studies have indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 70 publications
(126 reference statements)
0
40
0
Order By: Relevance
“…Yeast two‐hybrid (Y2H) assays were performed as described previously by Zheng et al . (2022). The pGBKT7‐MYB43 and pGADT7, and pGBKT7‐MYB43 and pGADT7‐ICE1 construct combinations co‐transformed into the yeast strain AH109, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast two‐hybrid (Y2H) assays were performed as described previously by Zheng et al . (2022). The pGBKT7‐MYB43 and pGADT7, and pGBKT7‐MYB43 and pGADT7‐ICE1 construct combinations co‐transformed into the yeast strain AH109, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…MYB proteins are key factors in regulatory networks controlling development, metabolism, and responses to biotic and abiotic stresses (Jin et al ., 2000; Jung et al ., 2008; Dubos et al ., 2010; Baek et al ., 2013; Zheng et al ., 2022). Our previous study found that MYB43 negatively regulates cadmium (Cd) stress tolerance by inhibiting the expression of HMAs (Zheng et al ., 2022). Furthermore, PLEIOTROPIC REGULATORY LOCUS 1 (PRL1), a WD‐40 protein, was identified as an important pleiotropic regulator of plant responses to sugars, multiple hormones, biotic and abiotic stress (Németh et al ., 1998; Lee et al ., 2008; Flores‐Pérez et al ., 2010), and as a substrate receptor of the CUL4‐DDB1‐PRL1 (CRL4 PRL1 ) E3 ligase complex to degrade KIN10 (Bhalerao et al ., 1999; Lee et al ., 2008), interact with, and promote degradation of MYB43 (Zheng et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we found 41 genes were commonly up-regulated in P. alba and P. russkii under salt stress ( Figure 4 c), including some transcription factors/genes that were important for response to osmotic stress, abscisic acid, or abiotic stress, such as MYB43/78, WRKY48, bZIP1, Responsive to Dessication 26 (RD26a/b), Highly ABA-Induced PP2C Gene 1 (HAI1), Drought-Induced 21 (DI21), and Late Embryogenesis Abundant 4-5 (LEA4-5) [ 28 , 29 , 30 , 31 , 32 ]. There were 20 genes commonly downregulated in P. alba and P. russkii under salt stress, including several that were previously reported to play an important role in ion homeostasis and root development, such as Vacuolar iron Transporter-Like 2 (VTL2), Ferric Reductase Defective 3 (FRD3), Nitrate Reductase 1 (NR1), DWARF14-LIKE2 (DLK2), and GRAS [ 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The transcriptomic data identified many salt-tolerant candidate genes in poplars, including among them some important transcription factors previously reported under either osmotic stress or salt stress, i.e., RD26a/ANAC072, bZIP1, MYB78, MYB43, WRKY48, and GAPC2 ( Figure 4 c) [ 29 , 31 , 32 ], as well as consisting of several protein-encoding genes such as DI21, ABA-induced PP2C (HAI1)/SAG113, and the LEA4-5 which related to osmotic stress [ 30 ]. These genes maybe contribute to improve salt tolerance in forest and crop plants.…”
Section: Discussionmentioning
confidence: 99%
“…Some transcriptional regulatory genes have been shown to be associated with cadmium stress in other plants. For example, MYB43 negatively regulated cadmium tolerance in Arabidopsis by transcriptionally inhibiting the Cd transporters (HMA2, HMA3, and HMA4) (Zheng et al 2022). MYB49 positively affected Cd accumulation in A. thaliana by directly regulating the expression of bHLH38 and bHLH101, and subsequently activating IRT1 transcription (Zhang et al 2019).…”
Section: ; Peng Et Al 2017amentioning
confidence: 99%